Improving the Quality of Education Based on the Role of the School Supervisor - Baili, Muhas; Sari, Siti Mayang; Zahraini; Musdiani (Universitas Veteran Bangun Nusantara, 2024)
This research reflects the government's initiative to improve access and quality of education in Indonesia, while catching up with more developed countries, and outlines the advantages and disadvantages of education in Indonesia compared to education abroad. The author adopts a research method using the literature study method as a form of preparation using references from various sources, including archives, the internet (both in digital and physical form), and books. The results of the research analysis show that support from all parties is needed to support the ongoing improvement process. Education in Indonesia has a unique identity and local policies that other countries do not have. Even though PISA data shows that the quality of education in Indonesia is still far behind, this does not reduce the enthusiasm of all parties to continue to improve quality. Each system has advantages and disadvantages, and the system implemented should be adapted to the conditions in each region, while maintaining local policies that need to be preserved.